MICROSOPHY OF POWER IN THE CONTEXT OF SCIENTIFIC AND EDUCATIONAL SPACE - L. V. Krymets (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The article is aimed to actualize the value of microsophy as the new direction of philosophical research, to analyze scientific and educational reality. Methodology. In terms of methodology used in the study, the focus was on identifying the theoretical positions that lead conceptuality, systematic approaches to understanding existing scientific and educational space, to clarify the essential aspects that underlie this phenomenon. Analysis of the main trends of power relations in the scientific and educational space of transitive Ukrainian society, as well as assessment of possible prospects for development and further evolution of public relations, providing treatment to study the processes are still far from complete, actualized using probabilistic methods of social forecasting.Originality. Modern scientific and educational space is conceptualized as an interactive purposefully organized environment, the main subject of which is conscious, responsible and creative personality, is formed in the course of research and education. Decentralization of scientific and educational space is designated one of the important priorities of social development. The principle of decentralization of power involves the formation of a multidimensional system of mutual confrontation and daunting interdetermination of management, the main mechanism of which is social dialogue and self-organization. Conclusions. Scientific and educational environment is the context, measure and vector updating section majority of social management. It is a scientific and educational space formed by an active, purposeful and creative citizen who has to seek a conscious and responsible public administration and government, and to the faithful implementation of the management system will power relations. Postnonclassical scientific and educational reality is seen by us as a communicative area that has a dynamic structure and appears in instability and continuous interaction between different levels of development. Information scientific and educational reality represents itself as the world's fixed power relations within established social institutions, and in particular communicative virtual network elusiveness. That is why actualized the problem of determining the nature of power relations in the scientific and educational space. Microsophy as art micro social updating helps expand the ideological guidance in the defined context.